ANALISIS DAMPAK POLIGAMI DALAM KEHARMONISAN RUMAH TANGGA: STUDI KASUS DI KECATAMAN KANIGARAN KOTA PROBOLINGGO - Hoiriyah, Rosidatul; Fida , Imanuddin Abil (LPPM STAI Muhammadiyah Probolinggo, 2023)
This article aims to examine the concept of the impact of polygamy on household harmony which is currently, widespread in people’s lives today. The family, as a unit formed from marriage, creates a relationship that is Sakinah, Mawadah, Warahmah. Polygamy, is a process in which a man has more than one wife at the same time, Islam allows it with certain conditions. However, the psychological impact on wives and children includes family conflict, competition between wives, as well as negative impacts on children’s development, including lack of love and trauma. Justice in polygamy is the key to preventing these negative impacts. Keywords: Polygamy; Impact of Polygamy; Family.